Aplicação da abordagem lean no processo de desenvolvimento de produtos de uma indústria metal mecânica - Schleder, Giancarlo Stefani (2021)
With the greater longevity of the population and the increase in surgical procedures who need the use of bone grafts and prostheses, the search for bone material for a biological reconstruction becomes necessary. Several researchers have worked with the use of lyophilized bone as a bone substitute, with promising results. At the UPF bioengineering, biomechanics and biomaterials laboratory, research involving this biomaterial in the form of powders with binders throughout the last years. Thus, equipment for obtaining bone powder is also a focus of researches. Projects applied to the production of a chipper, grinder and sieving that produce the bone powder with the necessary characteristics, having as little as possible. handling, are necessary. For this purpose, a machine was designed and produced. low cost multifunctional, with chopper, grinder and sieving system coupled, with the product passing from one process to the other with a minimum of handling, using gravity. At the end of the process, the bone powder can be arranged in packaging or go straight to 3D printing. In this way, we obtained a powder of bone with adequate properties and with the necessary granulometry for use in 3D printing (around 50 microns). The machine was developed in 304 stainless steel in the parts where there is contact with the components of the biomaterial (bone). the passage of one process to the other was organized in such a way as to have minimal handling. At the During the research and the project, a compact machine with mechanisms was chosen. simple. Thus, using the least amount of welds and easy assembly processes, the costs have been reduced. In the experimentation phase, with a series of settings mainly in milling, the machine presented the expected results regarding the production time and product quality, producing the 50 micron bone powder with little handling from one process to another.